Penerapan Metode HIRA (Hazard Identification and Risk Assessment) dalam Keselamatan dan Kesehatan Kerja di PT. GECE - Iskandar, Iqhman Said; Kusnadi, Kusnadi (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
The application of the HIRA Method has a crucial role in efforts to improve occupational safety and health in industrial environments. This research aims to analyze the impact of implementing HIRA in identifying potential hazards and evaluating risks related to company operational activities. The research method involves data related to accidents, mear-accidents, as well as work processes and equipment used. The research results show that the effective application of HIRA can identify various potential hazards that may occur in the workplace. Overall, this research presents evidence that the application of the HIRA Method has a significant positive impact on occupational safety and health. The recommendations of this research include carrying out strict and disciplined supervision of work safety monitoring, as well as training on the importance of implementing K3 when working so that workers can work safely dan securely Keywords: Dangers and Risk, HIRA (Hazard Identification and Risk Assessment), Occupational Safety and Health